Generating Enteric Nervous System Progenitors from Human Pluripotent Stem Cells. Issue 6 (8th June 2021) - Gogolou, Antigoni; Frith, Thomas J.R.; Tsakiridis, Anestis
Abstract: The intrinsic innervation of the gastrointestinal (GI) tract is comprised of enteric neurons and glia, which are buried within the wall of the bowel and organized into two concentric plexuses that run along the length of the gut forming the enteric nervous system (ENS). The ENS regulates vital GI functions including gut motility, blood flow, fluid secretion, and absorption and thus maintains gut homeostasis. During vertebrate development it originates predominantly from the vagal neural crest (NC), a multipotent cell population that emerges from the caudal hindbrain region, migrates to and within the gut to ultimately generate neurons and glia in response to gut‐derived signals. Loss of GI innervation due to congenital or acquired defects in ENS development causes enteric neuropathies which lack curative treatment. Human pluripotent stem cells (hPSCs) offer a promising in vitro source of enteric neurons for modeling human ENS development and pathology and potential use in cell therapy applications. Here we describe in detail a differentiation strategy for the derivation of enteric neural progenitors and neurons from hPSCs through a vagal NC intermediate. Using a combination of instructive signals and retinoic acid in a dose/time dependent manner, vagal NC cells commit into the ENS lineage and develop into enteric neurons and glia upon culture in neurotrophic media. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Generation of vagal neural crest/early ENS progenitors from hPSCs Basic Protocol 2 : Differentiation of hPSC‐derived vagal NC/early ENS progenitors to enteric neurons and glia